2021
DOI: 10.26803/ijlter.20.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Constructivist Learning Amid the COVID-19 Pandemic: Investigating Students’ Perceptions of Biology Self-Learning Modules

Abstract: Modes of teaching and learning have had to rapidly shift amid the COVID-19 pandemic. As an emergency response, students from Philippine public schools were provided learning modules based on a minimized list of essential learning competencies in Biology. Using a cross-sectional survey method, we investigated students’ perceptions of the Biology self-learning modules (BSLM) that were designed in print and digitized formats according to a constructivist learning approach. Senior high school STEM students from gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…Our findings on the issue confirmed that it had changed significantly. There is an opinion that students should construct their knowledge for themselves (Funa & Talaue, 2021), and they must be ready for self-directed learning (Melkonian, 2022). As we suggested above, the teacher plays the role of a facilitator and organizer, focusing on collaborative and communicative activities.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on the issue confirmed that it had changed significantly. There is an opinion that students should construct their knowledge for themselves (Funa & Talaue, 2021), and they must be ready for self-directed learning (Melkonian, 2022). As we suggested above, the teacher plays the role of a facilitator and organizer, focusing on collaborative and communicative activities.…”
Section: Discussionmentioning
confidence: 99%
“…Principles of constructivist pedagogy have been adopted in numerous educational innovations, including problem-based learning, project-based learning, inquiry-based approach and design thinking. Problem-based learning has a significant and positive effect on students' academic performance, achieving higher marks on all assessments than the control group who experienced traditional approach, according to a meta-analysis of studies, mostly from Asia, conducted from 2016 to 2020 (Funa and Prudente, 2021). Ayaz and Sekerci's (2015) analysis of studies from 2003 to 2014 suggest the effectiveness of constructivist learning approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As one study found, although students had better grades as they progressed through the semesters, they still experienced a decrease in peer negotiations and social support (Zuckerman et al, 2021). Other findings showed difficulties in using self-learning modules, as indicated by unfamiliar words, a lack of supporting resources, and slow internet connections, which imposed additional demands on teachers to create a productive learning environment (Funa & Talaue, 2021). These findings point to the necessity of further exploring other critical aspects of self-regulated learning, such as basic psychological needs, in order to maintain a constructivist environment.…”
Section: And Selfdetermined Learning In the Flipped Classroom During...mentioning
confidence: 99%